(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
The variety of financial technology (FinTech) companies and their activities poses heterogeneity in the business models of them. Not only the business environment has been changing rapidly, the financial services sector influences and triggers changes as well. And it is hard to determine whether and which changes influence the business model disruptively and which evolutionary. To enable management decision making easier, methodology for identification of possible microeconomic risks and their influence on the current activity and the whole business model of the company has to be shaped accordingly. The aim of this research is to find out what and how microeconomic factors affect business modelling of the FinTech companies. In this research the authors used a continuous comparative analysis method as well as content analysis method [1]. In interviews, experts were asked to assess the significance of specific microeconomic factors by using the Likert's scale. As a result of the research, the difference of the influence as well as their dependencies and modifications on business modelling was determined. This result forms the basis for conclusions about the most important microeconomic impact factors, the areas of their influence and possible consequences that affect business modelling of the FinTech company.